Institutional design propositions for the governance of adaptation to climate change in the water sector - Patrick Huntjens (2018)
This paper provides an evidence-based contribution to understanding processes of climate change adaptation in water governance systems in the Netherlands, Australia and South Africa. It builds upon the work of Ostrom on institutional design principles for local common pool resources systems. We argue that for dealing with complexities and uncertainties related to climate change impacts (e.g. increased frequency and intensity of floods or droughts) additional or adjusted institutional design propositions are necessary that facilitate learning processes. This is especially the case for dealing with complex, cross-boundary and large-scale resource systems, such as river basins and delta areas in the Netherlands and South Africa or groundwater systems in Western Australia. In this paper we provide empirical support for a set of eight refined and extended institutional design propositions for the governance of adaptation to climate change in the water sector. Together they capture structural, agency and learning dimensions of the adaptation challenge and they provide a strong initial framework to explore key institutional issues in the governance of adaptation to climate change. These institutional design propositions support a " management as learning" approach to dealing with complexity and uncertainty. They do not specify blueprints, but encourage adaptation tuned to the specific features of local geography, ecology, economies and cultures. © 2011 Elsevier Ltd.